2021
DOI: 10.1038/s41598-020-79741-w
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of muscle blood flow and O2 uptake via near-infrared spectroscopy using a novel occlusion protocol

Abstract: We describe here a novel protocol that sequentially combines venous followed by arterial occlusions to determine muscle blood flow and O2 uptake from a single measurement point using near-infrared spectroscopy (NIRS) during handgrip exercise. NIRS data were obtained from the flexor digitorum superficialis (FDS) muscle on the dominant arm of 15 young, healthy adults (3 women; 26 ± 7 years; 78.6 ± 9.1 kg). Participants completed a series of 15-s static handgrip contractions at 20, 40 and 60% of maximal voluntary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…These questions, partially explained by time-related technological limitations, motivated RH exploration with other instruments in addition to plethysmography and laser Doppler flowmetry. RH has been investigated with near-infrared spectroscopy (NIRS) [ 28 , 29 ] and compared with PAT [ 30 ], assessed with diffuse correlation spectroscopy (DCS) [ 31 ], contrast-enhanced ultrasound (CEUS) [ 32 ], and peripheral artery tonometry [ 33 ]. Although these studies confirm the possibility of the use of quantifiable metabolic and molecular variables, together with image(s), in clinical and preclinical settings, there is still no agreement about outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These questions, partially explained by time-related technological limitations, motivated RH exploration with other instruments in addition to plethysmography and laser Doppler flowmetry. RH has been investigated with near-infrared spectroscopy (NIRS) [ 28 , 29 ] and compared with PAT [ 30 ], assessed with diffuse correlation spectroscopy (DCS) [ 31 ], contrast-enhanced ultrasound (CEUS) [ 32 ], and peripheral artery tonometry [ 33 ]. Although these studies confirm the possibility of the use of quantifiable metabolic and molecular variables, together with image(s), in clinical and preclinical settings, there is still no agreement about outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Stronger correlations for the “time-to-peak” variable from CEUS and NIRS were recently reported [ 32 ]. Moreover, the venous and arterial involvement in RH is still not properly controlled in typical procedures, meaning that the vascular responsiveness of both micro and macrocirculation at different depths cannot be clearly distinguished [ 17 , 28 , 29 , 34 , 35 ]. Additionally, recent data from DCS suggests that skin circulation is not the best model to study skeletal muscle vasculature by RH [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous occlusion technique has been suggested to estimate O 2 supply and consumption in working muscles during exercise ( Homma et al, 1996 ). Similarly, a recent study demonstrated that combination of arterial and venous occlusion provides valid estimates of blood flow and oxygen consumption at rest and during exercise ( Dennis et al, 2021 ). Although we must acknowledge that these techniques are useful and that we should have performed this technique to obtain more insight interpretations, we considered that further arterial occlusion may not be required after exhaustion.…”
Section: Discussionmentioning
confidence: 94%
“…It is difficult to have confidence in conclusions drawn from the studies identified in this review with so few data points. It should be acknowledged that a wider body of literature that has examined the use of NIRS based methods to measure blood flow in other tissues does exist and should, to some degree, bolster confidence in the findings of the studies identified in this review (Choo et al, 2017;Bangalore-Yogananda et al, 2018;Dennis et al, 2021).…”
Section: Limitations Of the Literaturementioning
confidence: 85%